Geographical Imaginations of the Mediterranean Along Dichotomies of East-West/North-South - (:unkn) unknown (My University, 2018)
This article endeavours to analyse the European and Turkish discourses regarding the concept of the“Mediterranean” and its variations both in temporal and spatial terms. The theoretical inspirationof this article comes from the “geographical imagination as a way of thinking about world politicsand considering the relative importance of places and the relationships between contested narrativesof a specific region or territory”. Hence this study will examine different geographical imaginationsof the Mediterranean region that are projected onto both Turkish and European political discourse.The perspective which is engaged here involves the historical geography, or geosophy put forward byJ. K. Wright (1946) who assumed that geographical knowledge is not only a knowledge of physicalcharacteristics and natural resources, but is also something being defined and redefined by thepolitical imagination of the perceiver. So in this article a “geosophical” perspective will be applied to theMediterranean region that plays both a historical and strategic role in Euro-Turkish relations

Bu makalede Avrupa Birliği ve Türkiye’nin siyasal söyleminde “Akdeniz” kavramı mekânsal ve tarihsel boyutlarıyla ele alınıyor. Makalenin teorik zemini dünya siyasetinde coğrafi imgelemin oynadığı rollerden ilham alıyor. Bir tahayyül olarak coğrafi anlatılar zaman zaman örtüşen zaman zaman çatışan eksenlerde karşımıza çıkabiliyor; makalede Akdeniz örneğine bakarak Avrupa ve Türk söyleminin bu bölgeyi nasıl tahayyül ettiği tarihsel ve siyasal anlatıların nerelerde çakışıp nerelerde birbirinden ayrıldığı konu edilmekte. Konuya yaklaşım şekli J.K Wright’in “jeozofi” olarak adlandırabileceğimiz perspektifinden güç alıyor. Jeozofik yaklaşım sayesinde coğrafi epistemolojinin sadece fiziksel ve doğal kaynaklardan ibaret olmadığı, insan tahayyülünün de coğrafi bilginin şekillendirici bir parçası olduğu tartışılıyor. Böylelikle AB – Türkiye ilişkilerinde önemli rol oynayan “Akdeniz” anlatısı ve bu bölgeye dair stratejiler iki farklı açıdan tartışmaya açılıyor.
Doğu-Batı/Kuzey-Güney İkilikleri Çerçevesinde Coğrafi Bir Tahayyül Olarak Akdeniz
Keywords: Uluslararası İlişkiler; Siyasi Bilimler